PHOTOMETRY AND THE BLAZHKO EFFECT IN THE RR Lyr VARIABLE STAR Y Vul - Udovichenko, S N.; Keir, L. E. (Одеські астрономічні публікації, 2020)
The RR Lyr variable star Y Vul have been observed by using a CCD photometer during sev- eral seasons from 2011 to 2017. Nearly 5960 data points were obtained spanning over 53 nights. We found the amplitude and phase modulations with the amplitudes of 0.16 mag and 0.041 of the pulsating phase in V fil- ter; 0.15 mag and 0.041 of the pulsating phase in R filter, respectively. The frequency Fourier analysis of the light curves with the help of Period04 software was performed, Blazhko modulation period (59.20 days) and triplet structures in the Fourier spectrum were de- tected. The pulsation frequency components in the Fourier spectrum were identified up to the 7th har- monic order, while the modulation side lobe frequen- cies – up to 9th order. The analysis of the light curves maxima resulted in the same value of the Blazhko pe- riod.Thefundamental pulsation period of the star has been practically stable over a period of a hundredyears.